Real-World Data on the Prevalence of Anaplastic Lymphoma Kinase–Positive Non–Small-Cell Lung Cancer in the Middle East and North Africa. (2021) - Jazieh, Abdul Rahman; Gaafar, Rabab; Errihani, Hassan; Jaafar, Hassan; Al Dayel, Fouad; Bahnassy, Abeer A.; El Kadi, Hatem; Abdallah, Mohamed Magdy; Zaatari, Ghazi
Abstract : PURPOSE: Anaplastic lymphoma kinase ( ALK ) gene alterations are potent oncogenic drivers in non–small-cell lung cancer (NSCLC). Tyrosine kinase inhibitors targeting the ALK pathway are effective in treating ALK -positive NSCLC. Around 5% of Asian and White patients with NSCLC have ALK -positive tumors, but ALK rearrangement prevalence data in the Middle East and North Africa (MENA) region are limited. METHODS: In this noninterventional epidemiology study, histologically confirmed nonsquamous NSCLC samples retained for < 5 years in tissue banks at six centers in MENA were retrospectively analyzed for ALK rearrangement using the VENTANA immunohistochemistry (IHC) method. Patient characteristics obtained were analyzed for association with ALK rearrangement. Concordance between IHC and Vysis fluorescence in situ hybridization (FISH) ALK detection methods was assessed in a subset of samples. RESULTS: Four hundred forty-eight tissue samples were analyzed using IHC: 137 (30.6%) in Lebanon, 104 (23.2%) in Saudi Arabia, 97 (21.7%) in Egypt, 80 (17.9%) in the United Arab Emirates, and 30 (6.7%) in Morocco. On the basis of IHC, the prevalence was 8.7% (95% CI, 6.3 to 11.7) for ALK -positivity and 91.3% (95% CI, 88.3 to 93.7) for ALK -negativity. On the basis of FISH (n = 148), the prevalence was 5.4% positivity and 81.8% negativity (12.8% nonevaluable). Concordance between IHC and FISH (n = 129) was 98.4% (95% CI, 94.2 to 99.8) for negative agreement and 98.5% (95% CI, 94.5 to 99.8) for overall agreement. Univariate analysis showed that ALK rearrangement was significantly associated with epidermal growth factor receptor wild-type status ( P = .03) but was not significantly associated with sex, race, smoking history, or histologic subtype. CONCLUSION: Our findings suggest that ALK rearrangements are more prevalent in MENA than other geographic regions. High concordance was found between FISH and IHC. Except for epidermal growth factor receptor wild-type status, no clinicopathologic characteristics were associated with ALK -positive NSCLC.